Biodegradation of (Aminomethyl)phosphonic acid (AMPA) by isolated microbial consortia extracted from biological filters at drinking water treatment plants - Pickering, Laura; Folkes, Miles; Holden, Barrie; Jarvis, Peter; Campo Moreno, Pablo; Hassard, Francis (Elsevier, 2024)
The widespread use of glyphosate has significantly increased its presence in drinking water sources. Aminomethylphosphonic Acid (AMPA), a breakdown product of glyphosate, is challenging to remove from water using conventional treatment methods, posing risks to public health and environmental safety. This work investigates the biodegradation of AMPA by bacteria isolated from three environmental sources, with a focus on determining their potential application in water treatment systems. Two samples were collected from granular activated carbon (GAC) filters of different operational durations at a water treatment facility, and one sample was taken from soil that had historically been treated with glyphosate-based herbicides. Bacterial isolates capable of degrading AMPA were identified from these samples through selective enrichment, and kinetic degradation experiments were then conducted to assess their effectiveness. In environmental samples, after 48 hrs AMPA removal was > 70 % using GAC from an active treatment plant and soil samples removed 19 %. After bacterial isolation a consortium was isolated and from these four isolates were identified, comprising three species, including novel AMPA degraders M−S3 and M−SS (Myroides sp. mNGS23), and P-S92 (Pseudochrobactrum saccharolyticum). Within both minimal media supplemented with AMPA and raw untreated showing substrate concentrations above 10 mg/L whilst the specific degradation rates saw a decrease in substrate concentrations above 100 mg/L. AMPA removal occured in pilot scale sand filters augmented with P-S92 but removal was inconsistent. These findings show the potential of using biodegradation as an effective treatment strategy for AMPA removal from water. The identification of AMPA-degrading bacteria offers a promising solution for enhancing the removal of this persistent pollutant from contaminated waters. Further research is recommended to explore the full-scale application of these isolates in water treatment processes. This study contributes to the development of sustainable water treatment technologies by harnessing the natural degradative capacities of environmental bacteria.
Keywords: 4105 Pollution and Contamination; 40 Engineering; 41 Environmental Sciences; 4004 Chemical Engineering; 4011 Environmental Engineering; Aminomethylphosphonic acid (AMPA); Micropollutant removal; Pesticide; Selective Isolation; Enrichment; Drinking Water Treatment